Literatur Review : Perbandingan Asupan Protein Hewani dan Protein Nabati pada Balita Stunting di Indonesia - Vivi Indah Purnamasari; Fatmalina Febry (Malahayati Nursing Journal, 2023)
ABSTRACT Stunting is a condition in which children experience impaired growth as a result of chronic nutritional problems, namely lack of nutritional intake for a long time. This study aims to determine the comparison of intake of animal protein and vegetable protein in stunted toddlers. Literature review is conducted by searching, summarizing, and combining the core of several scientific sources that are accurate and valid from search databases such as Google Scholar and Garuda Portal. The literature searched for is limited from 2015 to 2022 with the keywords "Stunting". "Toddlers", "Animal Protein", "Vegetable Protein" both in Indonesian and English. Literature was analyzed using a matrix table. Stunted toddlers tend to consume vegetable protein compared to animal protein. Stunted toddlers consume vegetable protein because it is cheap, easy to get, area of residence, and parents income. Keywords: Stunting, Protwin Intake, Toddler, Animal Protein, Vegetable Protein ABSTRAK Stunting adalah suatu kondisi dimana anak mengalami gangguan pertumbuhan sebagai akibat dari masalah gizi kronis yaitu kekurangan asupan gizi dalam waktu yang lama. Penelitian ini bertujuan untuk mengetahui perbandingan asupan protein hewani dan protein nabati pada balita stunting. Tinjauan Literatur dilakukan dengan cara mencari, meringkas, serta menggabungkan inti dari beberapa sumber ilmiah yang akurat dan valid dari database pencarian seperti Google Scholar dan Portal Garuda. Literatur yang dicari dibatasi dari tahun 2015 sampai tahun 2022 dengan kata kunci "Stunting”. “Balita”, “Protein Hewani”, “Protein Nabati” baik dalam Bahasa Indonesia maupun Bahasa inggris. Literatur dianalisis dengan menggunakan tabel matriks. Balita stunting cenderung mengkonsumsi protein nabati dibandingkan dengan protein hewani. Balita stunting mengkonsumsi protein nabati diakarenakan harga yang murah, mudah didapatkan, wilayah tempat tinggal, dan pendapatan orang tua.  Kata Kunci: Stunting, Balita, Protein Hewani, Protein Nabati